A Uniformed DC Magnetic Generator Using Ferromagnetic Slot Cage by Geomagnetism Distortion Cancellation - Seog Y. Jeong; Seung-Hwan Lee; Eun S. Lee (IEEE Access, 2022)
A widely uniform and highly ambient robust DC magnetic field generator for precise motion sensors using inertial measurement units (IMUs) is newly proposed in this paper. Chronic problems such as low uniformity of magnetic field and geomagnetic disturbance of conventional Helmholtz, Merritt, Rubens, Lee-Whiting, and Tetra coils can be significantly mitigated by the proposed uniform DC magnetic field generator (UFG). Different from the previous air coils, the proposed UFG adopts a core-cage so that a strong and uniform DC magnetic field distribution can be generated inside the cage and that the UFG may be quite magnetically robust to ambient changes such as geomagnetic field and ferromagnetic objects. A dedicated power supply was developed for providing not only a DC current to generate the required magnetic field but also an exponentially decaying AC current to demagnetize the residual magnetic field in the core-cage. Design procedures for the UFG are fully established, considering the manufacturing cost, performance, and mechanical robustness for commercialization. Detailed designs of the UFG for magnetic field generation, enhancing uniformity, geomagnetic cancellation, and demagnetizing of the UFG are provided. Experimental results verified by a 30 cm $× $ 30 cm $× $ 30 cm prototype UFG showed that the geomagnetic field inside the UFG was significantly attenuated by 22 dB while the DC magnetic field uniformity ( $θ _{t}< 5.0^{° }$ ) was achieved over 85% of the total volume of 27,000 cm3.